Real-time study of protein adsorption kinetics in porous silicon - Lasave, Liliana Carolina (2013)
This paper presents an optical method for real-time monitoring of protein adsorption using porous silicon self-supported microcavities as a label-free detection platform. The study combines an experimental approach with a physical model for the adsorption process. The proposed model agrees well with experimental observations, and provides information about the kinetics of diffusion and adsorption of proteins within the pores, which will be useful for future experimental designs